Effect of sodium acetate, chilli and turmeric on the shelf life of refrigerated tilapia fillet - Tuan Zainazor Tuan Chilek,; Amiza Mat Amin,; Norhidayah Jusoh,; Suhana Muhamad Hanidun,; Nasrenim Suhaimin,; Zarina Mohd Shariff,; Saadiah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to determine the effects of turmeric powder, chilli powder and sodium acetate on the shelf life of refrigerated tilapia fillets at 5ºC. Six treatments were applied to the tilapia fillets which were salt (S), salt and turmeric (ST), salt and chilli (SC), salt, turmeric and sodium acetate (STNaA) and salt, chilli and sodium acetate (SCNaA) and control. The samples were analyzed in 15 days period for microbiological, chemical and physical analyses. It was found that there were significant differences (p<0.05) in all microbiological analysis of fish treated with STNaA and SCNaA compared to other treatments. Microbiologically, the shelf life of fillets treated with STNaA and SCNaA was 12 days, fillets treated with ST, SC and S were 6 days, and only 3 days for control fillet. In terms of TVB-N and TMA values, ST fillets were still acceptable up to 12 to 15 days of refrigerated storage. As for TBA values, they were in acceptable range for all treatments throughout 15 days storage. The texture quality in decreasing order was given by fillets with SCNaA, SC, STNaA, ST, S and control treatment. In conclusion, the best treatment to extend the shelf life of refrigerated Tilapia fillet was given by STNaA, followed by SCNaA and ST.